Teachers’ Perception and Readiness Toward IPAS Learning Implementation of the Merdeka Curriculum - Izzah Muyassaroh; Aprilia Eki Saputri; Asep Saefudin; Nana Djumhana; Ira Rengganis; Mela Darmayanti (Universitas Sebelas Maret, 2023)
This qualitative descriptive research aims to explore teachers’ perceptions and preparedness for implementing the IPAS learning approach in the context of the MC. The subjects of this study were 87 elementary school teachers in Bekasi District who were selected through a purposive random sampling technique. Data collection was carried out through observation, interviews, and questionnaires. The collected data were then analyzed using interactive qualitative data analysis techniques, including data collection, presentation, and conclusions drawing. The results show that teacher readiness in the curriculum structure understanding is 24% in the high category, 69% medium, and 7% low. In lesson plan aspect, 27% are in the high category, 67% medium, and 6% low category. In the aspect of understanding of differentiated learning, 32% are in the high category, 55% medium, and 13% low. In terms of understanding of P5, 24% are in the high category, 63% medium, and 13% low. Regarding understanding of the Merdeka Mengajar platform, 18% in high category, 44% medium, and 38% low. Teachers' understanding regarding the IPAS assessment are 55% in the high category, 42% medium, and 3% low. Teachers are quite ready to organize science learning in MC implementation and show positive perception.